Changes of Vegetation Distribution in the East Dongting Lake After the Operation of the Three Gorges Dam, China - Hu, Jia-Yu; Xie, Yong-Hong; Tang, Yue; Li, Feng; Zou, Ye-Ai (Frontiers in Plant Science, 2018)
Water regime is regarded as the primary factor influencing the vegetation distribution in natural wetland ecosystems. However, the effect of water regime change induced by large-scale hydraulic engineering on vegetation distribution is still unclear. In this study, multi-temporal TM/ETM+/OLI images and hydrological data from 1995 to 2015 were used to elucidate how the change in water regime influenced the vegetation distribution in the East Dongting Lake (EDTL), especially after the operation of the Three Gorges Dam (TGD) in 2003. Using unsupervised and supervised classification methods, three types of land cover were identified in the study area: Water & Mudflat, Grass, and Reed & Forest. Results showed that the total vegetation area in EDTL increased by approximately 78 km2 during 1995-2015. The areas of Reed & Forest and Grass exhibited a contrasting trend, dramatic increase in Reed & Forest but sharp decrease in Grass, particularly after the operation of TGD. The lowest distribution elevations of Grass and Reed & Forest decreased by 0.61 m and 0.52 m, respectively. As a result of water level variation, submergence duration increased at 20-21 m and 28 m elevations (1 to 13 d), but significantly decreased at 22-27 m and 29-30 m elevations (-3 to -31 d). The submergence duration of Grass and Reed & Forest was 246 d and 177 d, respectively. This study indicated that wetland vegetation pattern significantly changed after the operation of TGD, mainly as a result of changes in submergence condition. Submergence duration might be an effective indicator to predict the shift of vegetation distribution in EDTL, and which could provide scientific guidance for vegetation restoration and wetland management in this lake.